The Mystery behind “Yawning”: A Physiological Insight - Dhar, Dipak Kumar; Arora, Ritik (Journal of Health and Allied Sciences NU, 2020)
Yawning is a very ubiquitous yet very poorly understood phenomenon. Even though with advancements in science, the scientific community has been able to decode the mechanisms and mysteries behind most of the physiological functions of the body, but we still do not have clear answers to this common activity that all of us experience numerous times on a daily basis. It is the enigma surrounding yawning that makes it all more intriguing. A lot of hypotheses and theories have been proposed since the times of Hippocrates. With more modern neuroimaging methods and bioassays available now, more meticulous inquiry is being increasingly made to elucidate a rational and scientifically sound physiological basis of yawning. A comprehensive and exhaustive study of articles and research work available on the internet on the subject was made through various search engines such as Google Scholar, PubMed, etc. This article attempts to provide in a nutshell the available information and knowledge on the subject and discuss its plausibility and the future direction of research in this field.
Keywords: yawning; mirror neuron system; arousal